Use of Antenatal Services among Women in Farming Communities in Kogi State - Muhammed K. Ibrahim; Ezekiel Haruna; Safiyat E. Tanko (Newinera Publisher, 2021)
This study examined the use of antenatal services among women in farming communities in Kogi State, Nigeria. A multi-stage sampling technique was employed to collect primary data from 150 randomly selected farmers through the use of structured questionnaire. The data was analysed using descriptive statistics and logit regression model. Analysis of socio-economic variable revealed that majority (73.4%) of the respondents were below the age 40 years, with a mean household size of 6 members. About 94.7% of the respondents used antenatal care services covering an average distance of 4km in getting to nearest health facility. The study also revealed that majority (92.7%) of the respondents were aware of healthcare facilities availability and they mostly got their information from family members and friends. The use of antenatal care services among women was high and majority (95.3%) of the respondents had the knowledge of where antenatal centre is located. Also majority of the respondents visited those centres in their last pregnancy with frequency of visit between 1- 4 times. Previous visits, nearness to ANC centres and formal education positively influence the use of ANC services among women in the study area. High cost of antenatal services and poor level of information were found to be the most significant challenges facing women access to antenatal care services. We recommend that government should subsidize health care services for women in order to improve their affordability.